RESEARCH ON BENDING⁃TORSION COUPLING VIBRATION CHARACTERISTIC OF COMPRESSOR SHAFT SYSTEM CONSIDERING HARD STIFFNESS CHARACTERISTIC - ZHANG Hao; ZHAO Xiang; ZHANG DongMei; ZUO Song (Jixie qiangdu)
In order to investigate the influence of the coupling variable stiffness characteristics on the vibration behavior of the shaft system， the motor rotor⁃coupling⁃crankshaft⁃bearing of the compressor was taken as the object of study， and the Lagrange method was used to construct a coupled dynamics model of the bending⁃torsion of the shaft system. The results show that the variable stiffness characteristics of the coupling will cause the phase space to appear as "sawtooth" fluctuations， but the law of variation of the shaft center trajectory was basically unaffected. With rotational speed as the control parameter， the variable stiffness characteristic induces nonlinear behaviors such as chaos and bifurcation and causes a rightward shift of the resonance peak and an increase in the amplitude of the unstable region. The degree of phase space fluctuation decreases with the reduction of the axial tile clearance， and the area of the non⁃contacting region in the x and y directions shows a decreasing trend. The research results can better predict the bending⁃torsion coupling vibration behavior of the shaft system and guide the selection of the operating speed of the shaft system.